Implementasi Mail Server Berbasis Squirrelmail Dengan Exchange Server Menggunakan Teknologi Virtualisasi di SMK Negeri 1 Pendalian IV Koto - Basorudin, Basorudin (UNIVED Press, 2018)
Server virtualization technology is the sharing of one physical machine by several server operating systems. The design and implementation of this mail server was built using Debian.5 as the base server operating system. The design and implementation of this mail server was built using a DNS server, web server and mail server/squirrelmail, configured using the help of the VirtualBox application as a server. DNS (Domain Name System) is a system that stores information about host names and domain names in the form of a distributed database on a computer network, for example the Internet. The application used to handle the delivery of mail messages is a mail server. This mail server always receives messages from the e-mail client used by the user, or perhaps from other e-mail servers. Web mail functions to send and view email messages via a web browser. Squirrelmail configuration is done by running the conf.pl script: /var/www/wemail/config/ conf.pl. Exchange Server services include: Directory Service, Simple Mail Transfer Protocol (SMTP), Post Office Protocol (POP3), IMAP (Internet Message Access Protocol), Complementary Services, System Attendant. For the Mail Server Delivery Process, see number 5.2.